Effect of seedbed solarization on plant growth and yield of two rice varieties–BR11 and BRRI Dhan33 - Neogi, M.G.; Uddin, AKM Salah; Uddin, M.T.; Lauren, J. (Bangladesh Academy of Sciences, 2017)
An experiment was carried out at RDRS Farm in Rangpur during the 2014 T. aman rice season to determine the impact of seedbed solarization on plant growth and yield of rice varieties, BR11 and BR33. Solarization was achieved by covering the seedbeds with transparent polythene sheet for four weeks prior to sowing. Seedlings of both varieties were raised on solarized and non-solarized seedbeds and later transplanted into the main field for comparison of growth and yield. Emergence, seedling height and weight, root length and weight were higher with seedlings raised on solarized seedbeds compared to seedlings from non-solarized seedbeds. Also root knot nematode galls decreased significantly on seedlings from solarized seedbeds compared to those from non-solarized seedbeds for both the varieties tested. The increase in height and weight of solarized seedlings enabled easy access for uprooting and transplanting seedlings in the main field within the recommended 20-25 days after sowing. When transplanted in untreated main fields, plants grown from the solarized seedlings of both the rice varieties had significantly less infestation of stem borer as compared to non-solarized plants. Grain yields obtained from solarized seedlings were 7% higher for BR11 and 9% higher for BR33 relative to normal seedlings.J. Bangladesh Agril. Univ. 15(1): 55-59, January 2017